Recommendations for the conduct of systematic reviews in toxicology and environmental health research (COSTER). (October 2020) - Whaley, Paul; Aiassa, Elisa; Beausoleil, Claire; Beronius, Anna; Bilotta, Gary; Boobis, Alan; de Vries, Rob; Hanberg, Annika; Hoffmann, Sebastian; Hunt, Neil; Kwiatkowski, Carol F.; Lam, Juleen; et al.
Highlights: COSTER is a set of recommendations for conduct of environmental health systematic reviews (EH SRs). COSTER's consensus process covered NGOs, academia, industry and government agencies. COSTER is intended for use by scientists, editors, agencies, and others seeking guidance on EH SRs. COSTER is put forward to initiate broader discussion of the EH community's expectations for SRs. COSTER is a first step in defining robust standards for good practice in conduct of EH SRs. Abstract: Background: There are several standards that offer explicit guidance on good practice in systematic reviews (SRs) for the medical sciences; however, no similarly comprehensive set of recommendations has been published for SRs that focus on human health risks posed by exposure to environmental challenges, chemical or otherwise. Objectives: To develop an expert, cross-sector consensus view on a key set of recommended practices for the planning and conduct of SRs in the environmental health sciences. Methods: A draft set of recommendations was derived from two existing standards for SRs in biomedicine and developed in a consensus process, which engaged international participation from government, industry, non-government organisations, and academia. The consensus process consisted of a workshop, follow-up webinars, email discussion and bilateral phone calls. Results: The C onduct of S ystematic Reviews in T oxicology and E nvironmental Health R esearch (COSTER) recommendations cover 70 SR practices across eight performance domains. Detailed explanations for specific recommendations are made for those identified by the authors as either being novel to SR in general, specific to the environmental health SR context, or potentially controversial to environmental health SR stakeholders. Discussion: COSTER provides a set of recommendations that should facilitate the production of credible, high-value SRs of environmental health evidence, and advance discussion of a number of controversial aspects of conduct of EH SRs. Key recommendations include the management of conflicts of interest, handling of grey literature, and protocol registration and publication. A process for advancing from COSTER's recommendations to developing a formal standard for EH SRs is also indicated.